UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI PONDOK PESANTREN SALAFIYAH - riyadi, sugeng; khalis, nur; ahmad, ahmad (UNISAN JURNAL, 2023)
The purpose of this study was to determine the quality of human resources to continually improve their quality continuously and continuously at the Salafiyah Islamic Boarding School. The data collection technique used is a qualitative method with a naturalistic approach which shows that the implementation of research occurs naturally, as it is, in normal situations that are not manipulated by circumstances and conditions, emphasizing natural descriptions. Data retrieval or phenomenon screening is carried out from reasonable conditions known as natural and natural retrieval. Based on the results of this study, it shows that the findings of data in the field show that the professionalism of teachers at the Salafiyah Islamic Boarding School is described in pedagogical abilities; namely the teacher's ability to prepare lesson plans, syllabus, Prota and Promissory notes, the ability to improvise learning methods and the ability to assess student learning outcomes through class-based assessments. Personality ability; illustrated by the inculcation of self-discipline and responsibility in assignments. Social ability; illustrated by good communication relationships with school principals, colleagues, parents of students and participation in social activities. While professional ability; illustrated by the ability to master the field of study seen from the educational background of teachers who have academic qualifications and teachers teach in accordance with their expertise and majors, the ability to understand students.